Digital pathology for primary diagnosis of screen‐detected breast lesions – experimental data, validation and experience from four centres. Issue 7 (12th May 2020) - Williams, Bethany; Hanby, Andrew; Millican‐Slater, Rebecca; Verghese, Eldo; Nijhawan, Anju; Wilson, Imogen; Besusparis, Justinas; Clark, David; Snead, David; Rakha, Emad; Treanor, Darren
Abstract : Aim: The rate of deployment of digital pathology (DP) systems for primary diagnosis in the UK is accelerating. The flexibility and resilience of digital versus standard glass slides could be of great benefit in the NHS breast screening programme (NHSBSP). This study aims to document the safety and benefits of DP for preoperative tissue diagnosis of screen‐detected breast lesions. Methods and results: Concordance data for glass and digital slides of the same cases from four sites were subjected to detailed concordance–discordance analysis. A literature review of DP in the primary diagnosis of breast lesions is presented, making this the most comprehensive synthesis of digital breast cancer histopathological diagnostic data to date. Detailed concordance analysis of experimental data from two histopathology departments reveals clinical concordance rates for breast biopsies of 96% (216 of 225) and 99.6% (249 of 250). Data from direct comparison validation studies in two histopathology departments, utilising the protocol recommended by the Royal College of Pathologists, found concordance rates for breast histology cases of 99.4% (180 of 181) and 99.0% (887 of 896). An intraobserver variation study for glass versus digital slides for difficult cases from the NHSBSP yielded a kappa statistic of 0.80, indicating excellent agreement. Discordances encountered in the studies most frequently concerned discrepancies in grading attributable to mitotic count‐scoring and identification of weddelite. Conclusions: The experience of four histopathology laboratories and our review of pre‐existing literature suggests that DP is safe for the primary diagnosis of NHSBSP breast histology specimens, and does not increase the risk of misclassification.